The Iterative Development and Testing of an Interactive Mobile Application for Skill Retention of Cardiopulmonary Resuscitation Among High School Students: A Pilot Study. (October 2021) - Arif, Adeel; Arif, Amber; Fasciglione, Kimberly Anne; Jafri, Farrukh Nadeem
Abstract: Background: Locations concentrated with High School (HS) students tend to have lower out-of-hospital cardiac arrest (OHCA) survival rates.Mobile applications (apps) have the capability to augmentcardiopulmonary resuscitation (CPR) skill retention as a low-cost, accessible training method. Methods: An iterative process to develop an app to reinforce CPR skills emphasizing hand placement, compression rate, real-time feedback, and recurring tips is described. The app was tested on HS students to measure its impact on quality and comfort of CPR using Likert surveys and skills assessments before and after one month of usage. CPR Score and compression rate were measured using the Laerdal™ Little Anne Manikin QCPR software. Results: Fourteen HS students participated in a prospective observational study. It was found that the use of the developed app was associated with improved CPR performance (80.43% v. 87.86%, p=0.01-0.02, 95% CI=2.20-12.66) after one month. Additionally, improvements were demonstrated in compression rate accuracy (21.43% v. 64.29%, p=0.041, 95% CI=0.132-0.725), increased comfort performing CPR (3.86 v. 4.79, p<0.001, 95% CI =0.99-1.00) and comfort performing CPR on strangers (2.71 v. 4.42, p<0.001, 95% CI=1.24-2.19). In addition, for every time the app was used, CPR performance increased by 0.5668% (p=0.0182). Conclusion: Findings suggest that mobile apps may have promising implications as augmentative tools for CPR curriculums.